Hawthorn Lace Bug, Corythucha cydoniae (Fitch) (Insecta: Hemiptera: Tingidae) - Frank W. Mead; Thomas R. Fasulo (EDIS)
Revised! EENY-080, a 4-page fact sheet by F.W. Mead and T.R. Fasulo, is part of the Featured Creatures collection. It describes this pest of woody, rosaceous plants in the northern part of Florida and across the U.S. — partial synonymy, distribution, identification, life history, hosts, detection notes, and management. Includes references. Published by the UF Department of Entomology and Nematology, March 2010.